APPLICATION OF AUDIO VISUAL METHOD TO IMPROVE STUDENTS' UNDERSTANDING OF PAI MATERIAL - Ahmad Fuad Abdul Baqi; Fareed Ahmad Obaidy (International Journal of Multidisciplinary Reseach, 2025)
The media has a very important role so that the position of the mass media becomes the main one in society. With the media, oral and written traditions in the learning process can be enriched with media such as audio-visual media, teachers can create various classroom situations, determine teaching methods that will be used in different situations and create a healthy emotional climate among students. In fact, this audio-visual media further helps teachers "bring" the world into the classroom. The learning method is an order or procedure that is arranged by educators regularly and systematically when delivering learning materials to students. The purpose of this study was to increase students' interest in learning PAI subjects at Miftahul Arifin Middle School by applying the audio visual method. In this study, the researcher used Classroom Action Research (CAR). From the results of the research that the researchers conducted, they were able to grow students' interest in learning in PAI subjects, namely by applying the audio-visual method. Student learning outcomes in cycle one reach an average of 7 5%, from this average value in the category that is still not finished, but in cycle two, student achievement increases by an average of 90% for the full type.